2010
DOI: 10.1136/bjo.2009.169284
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic, clinical and visual electrophysiological findings in children born to mothers prescribed substitute methadone in pregnancy

Abstract: Michael S Bradnam, et al.. Ophthalmic, clinical and visual electrophysiological findings in children born to mothers prescribed substitute methadone in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 23 publications
2
47
3
Order By: Relevance
“…Prolonged development of the brain makes the smooth pursuit function susceptible to influence from substrates operating during the fetal period. Previous studies have found an association between prenatal exposure to methadone and a condition of involuntary eye movements, which is assumed to interfere with the voluntary control needed in smooth pursuit 18,19. In the present study we found evidence of deviant smooth pursuit that we may relate to fetal exposure to methadone or buprenorphine, perhaps mediated by decreased availability of dopamine.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Prolonged development of the brain makes the smooth pursuit function susceptible to influence from substrates operating during the fetal period. Previous studies have found an association between prenatal exposure to methadone and a condition of involuntary eye movements, which is assumed to interfere with the voluntary control needed in smooth pursuit 18,19. In the present study we found evidence of deviant smooth pursuit that we may relate to fetal exposure to methadone or buprenorphine, perhaps mediated by decreased availability of dopamine.…”
Section: Discussionsupporting
confidence: 64%
“…The complexity of this process makes it particularly susceptible to impairment by a variety of factors, including the presence of teratogen substrates, such as tobacco, during the fetal period. Previous studies have found an association between prenatal exposure to methadone and nystagmus, suggesting that drug-exposed children may have difficulty controlling their eye movements 18,19. In addition, difficulties with smooth pursuit have been found in individuals suffering from schizophrenia 20.…”
Section: Smooth Pursuits and Saccadesmentioning
confidence: 99%
“…For example, they were up to 12-fold more likely to be admitted for strabismus and nystagmus. The underlying cause of visual disturbances in opioid-exposed children are unclear 23 but, if untreated, may lead to difficulties with self-image and social adjustment that intensifies to adulthood. 24 After NAS, children were also admitted more frequently for conditions that usually develop insidiously and which may not be apparent in early infancy, when medical and social surveillance of the high-risk mother and child is at its most intense.…”
Section: Discussionmentioning
confidence: 99%
“…Observed effects include strabismus, nystagmus and refractive errors as well as delayed visual maturation and cerebral visual impairment, and these may be associated with abnormal visual electrophysiology 3740. Although study numbers are small, nystagmus appears to be more common in those infants treated for NAS 38. The majority of infants with impaired visual development reported to date have been exposed in utero to both opiates and benzodiazepines and so it is impossible to determine exact aetiology.…”
Section: Long-term Implications For the Babymentioning
confidence: 99%